High magnetostriction and coupling coefficient for sintered cobalt ferrite derived from superparamagnetic nanoparticles - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Applied Physics Letters, 2012)
High magnetostriction (lambda) and coupling coefficient (d lambda/dH) of 315 ppm and 1.97 x 10(-9) A(-1) m, respectively, are obtained at room temperature for sintered cobalt ferrite derived from nanocrystalline powders. Also, the powder was compacted at a low pressure of 8 MPa and sintered for a short duration of 10 min at 1450 degrees C. Magnetic annealing at 300 degrees C in a field of 0.5 T for 30 min further enhanced the magnetostriction coefficient to 345 ppm with a higher coupling coefficient 2.12 x 10(-9) A(-1)m. The magnetic field above which maximum magnetostriction is observed is reduced by almost half after magnetic annealing. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4745922]

High magnetostriction coefficient of Mn substituted cobalt ferrite sintered from nanocrystalline powders and after magnetic field annealing - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Current Applied Physics, 2013)
Magnetostriction characteristics of Mn substituted cobalt ferrite, CoFe2-xMnxO4 (0 <= x <= 0.3), sintered from nanocrystalline powders of average particle size of similar to 4 nm have been studied. Larger value of magnetostriction at lower magnetic field is achieved after substitution of Mn for Fe. The maximum value of magnetostriction coefficient is not much affected and the slope of the magnetostriction is increased with increasing Mn content. Higher maximum value of magnetostriction coefficient (lambda) of 234 ppm comparable to that of the unsubstituted composition with larger strain derivative (d lambda/dH) is obtained for x = 0.2 in CoFe2-xMnxO4. The magnetostriction coefficient is increased to 262 ppm with further enhancement in the strain derivative after annealing the sintered compact at 300 degrees C in a magnetic field of 400 kA/m for 30 min. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; Magnetic field annealing; Magnetostriction; Mn substitution; Nanocrystalline

High magnetostriction parameters for low-temperature sintered cobalt ferrite obtained by two-stage sintering - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of Magnetism and Magnetic Materials, 2014)
From the studies on the magnetostriction characteristics of two-stage sintered polycrystalline CoFe2O4 made from nanocrystalline powders, it is found that two-stage sintering at low temperatures is very effective for enhancing the density and for attaining higher magnetostriction coefficient. Magnetostriction coefficient and strain derivative are further enhanced by magnetic field annealing and relatively larger enhancement in the magnetostriction parameters is obtained for the samples sintered at lower temperatures, after magnetic annealing, despite the fact that samples sintered at higher temperatures show larger magnetostriction coefficients before annealing. A high magnetostriction coefficient of similar to 380 ppm is obtained after field annealing for the sample sintered at 1100 degrees C, below a magnetic field of 400 kA/m, which is the highest value so far reported at low magnetic fields for sintered polycrystalline cobalt ferrite. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; Magnetostriction; Two-stage sintering